Basis and Principles of Systematic Thinking in Education - Mardianto Mardianto; Saiful Ahyar; Zainal Abidin (Universitas Muhammadiyah Enrekang, 2022)
This research is a literature study that examines the basic principles and principles of systematic thinking in education. background of the need for systematic thinking in the world of education, the results of the study show that in systems thinking, this structure (a set of causal circles) determines the behavior (behavior or dynamics) of a phenomenon. A positive causal circle will result in a growth or decline behavior. Positive causal loops are also known as Reinforcing loop types or use the